Are there differences in the attractiveness of shopping centres? Experiences from the Czech and Slovak Republics - Kunc Josef (Moravian Geographical Reports, 2016)
The measurement and evaluation of the attractiveness of shopping centres in the Czech and the Slovak Republics is examined in this paper, countries which had experienced seventy years of development within a single state. The methodological basis for measuring the attractiveness of 130 shopping centres is an evaluation of the factors that can be described as objective (exogenous and endogenous) and subjective (in vivo and in vitro approach). An aggregate indicator of the overall attractiveness of each shopping centre was computed as a combination of the sub-variables. Based on previous international studies, the factors (variables influencing attractiveness) that are typical for shopping malls anywhere in the world, as well as for the original specific information for the Czech-Slovak retail environment, enable a generalization of the results at least to the East Central European level, and to carry out a comparison with any other market environment.